Information accuracy and social welfare under homogeneous beliefs - Ng, David S. (Journal of Financial Economics, 1975)
This paper examines the ‘accuracy’ of information and its effect on social welfare. Information is defined to be more accurate than the existing information if individuals are willing to revise their subjective, homogeneous beliefs based on the new information. In a pure exchange economy where individuals may differ in endowments and tastes, it is shown that, for all utility functions satisfying risk aversion and non-satiation, the receipt of more accurate information does not increase social welfare (in terms of ex-ante Pareto-optimality) even when such information production is costless. This represents a more rigorous analysis on several issues that are not clear in the Marshall (1974) paper. Using the HARA class of utility functions, this paper also addresses the relationship between information and borrowing and lending, and the effect of information on the risk-free rate of interest.